Analysis of the mutually perturbed (31∏u, 41∏u) ← X1∑g+ band system in Li2 - Jędrzejewski-Szmek, Zbigniew; Grochola, Anna; Jastrzębski, Włodzimierz; Kowalczyk, Paweł (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Excitation spectra of the 31∏u and 41∏u states of the 7Li2 lithium dimer were measured. Polarization labelling spectroscopy was used to limit visible transitions to one or a few vibrational progressions. Positions of the observed spectra are consistent with previous measurements, but the assignment of quantum numbers to transitions is new. Adiabatic potentials were constructed, and the rovibrational levels were found to be perturbed by nearby ∑ states, but also by interaction between both ∏ states. Deperturbation analysis was attempted by extending the IPA method with a simultaneous treatment of two electronic states. Results of the deperturbation procedure are yet not fully satisfactory, but it is hoped that together with improved adiabatic potentials they will account for the positions of the observed energy levels.
Optica Applicata, Vol. 40, 2010, nr 3, s. 577-585
Keywords: optyka; diatomic molecules; polarization labelling spectroscopy; inverted perturbation approach